2013
DOI: 10.1177/2047487313481757
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific predictors of the prehypertension-to-hypertension progression: community-based cohort of a West-Asian population

Abstract: Easily-assessable, commonly-available information helped improve predictability of blood pressure measures for prehypertension-to-hypertension progression. Women's psycho-social characteristics (marital status) should be considered in prevention of prehypertension-to-hypertension progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…In a national survey, it was shown that 39.8% of Iranian subjects aged 25-70 years were prehypertensive [2]. Bozorgmanesh et al [36] reported that 5.6% of Iranian prehypertensive individuals develop hypertension annually. These findings and our results for SBP and DBP warn that preventive programs should focus on individuals with prehypertension.…”
Section: Discussionmentioning
confidence: 99%
“…In a national survey, it was shown that 39.8% of Iranian subjects aged 25-70 years were prehypertensive [2]. Bozorgmanesh et al [36] reported that 5.6% of Iranian prehypertensive individuals develop hypertension annually. These findings and our results for SBP and DBP warn that preventive programs should focus on individuals with prehypertension.…”
Section: Discussionmentioning
confidence: 99%
“…This condition is associated with an increased risk of cardiovascular and cerebrovascular diseases as well as total mortality ( 5 ). Pre-hypertension is highly prevalent in Iran (about 46% of Iranians aged 25 - 64) and considering its high progression rate of 56% over seven years to hypertension, it predicts an alarming trend ( 6 , 7 ). The data highlights the need for identifying the predisposing factors of pre-hypertension in Iranian populations.…”
Section: Introductionmentioning
confidence: 99%
“…Prehypertension and hypertension each affect about 30% of the world adult population and increase the risk of incidents of CVD [3, 5, 37]. According to a 7-year follow-up study of 25,079 prehypertensive people, the annual progression rate of prehypertension to hypertension is more than 5.5% [38]. Prehypertension is also a major risk for heart attacks, strokes, congestive heart failure, kidney failure, and cognitive decline [39–41].…”
Section: Discussionmentioning
confidence: 99%